Construction of Masculinities in the Discourse of Migrant Students in Chile [Construcción de Masculinidades en Los Discursos de Estudiantes Migrantes en Chile] - Contreras-Salinas, S; Ramirez-Pavelic, M (University of Warsaw, 2021)
The main objective of this paper was to identify the conceptions and representations associated with the construction of masculinity in the discourse and counter-discourse of male migrant students, aged between 12 and 14. To this end, a qualitative methodology was used in the form of group interviews and field notes. The data collected was analyzed from the standpoint of the discursive psychological approach of Korobov and Bamberg (2004), as well as discourse analysis. During this research it was possible to note the self-perception of children youths as being men in construction, and the non-existence of contributions from the school to the processes of construction of their masculinities. Another element to consider is the relevance that migrant students give to their family and particularly to the figure of the mother, mainly in terms of care and affection. Likewise, one of the main conclusions, in line with other research studies, reveals that, despite some exceptions, the students maintain a patriarchal idea of what it means to be a man and of his role in the social order, i.e. to keep the male imperative to procreate and provide. © 2021 University of Warsaw. All rights reserved.